Single dose GLP toxicity and biodistribution study of a conditionally replicative adenovirus vector, CRAd-S-pk7, administered by intracerebral injection to Syrian hamsters. Issue 1 (December 2016) - Kim, Julius; Auffinger, Brenda; Spencer, Drew; Miska, Jason; Chang, Alan; Kane, Joshua Robert; Young, Jacob; Kanojia, Deepak; Qiao, Jian; Mann, Jill; Zhang, Lingjiao; Wu, Meijing; et al.
Abstract Background CRAd-S-pk7 is a conditionally replicative oncolytic adenoviral vector that contains a survivin promoter and a pk7 fiber modification that confer tumor-specific transcriptional targeting and preferential replication in glioma while sparing the surrounding normal brain parenchyma. Methods This IND-enabling study performed under GLP conditions evaluated the toxicity and biodistribution of CRAd-S-pk7 administered as a single intracerebral dose to Syrian hamsters, a permissive model of adenoviral replication. Two hundred and forty animals were stereotactically administered either vehicle (n  = 60) or CRAd-S-pk7 at 2.5 × 107, 2.5 × 108, or 2.5 × 109 viral particles (vp)/animal (eachn  = 60) on day 1. The animals were closely monitored for toxicology evaluation, assessment of viral distribution, and immunogenicity of CRAd-S-pk7. Results Changes in hematology, clinical chemistry, and coagulation parameters were minor and transient, and consistent with the inflammatory changes observed microscopically. These changes were considered to be of little toxicological significance. The vector remained localized primarily in the brain and to some degree in the tissues at the incision site. Low levels of vector DNA were detected in other tissues in a few animals suggesting systemic circulation of the virus. Viral DNA was detected in brains of hamsters for up to 62 days. However, microscopic changes and virus-related toxicity to the central nervous system were considered minor and decreased in incidence and severity over time. Such changes are not uncommon in studies using adenoviral vectors. Conclusion This study provides safety and toxicology data justifying a clinical trial of CRAd-S-pk7 loaded in FDA-approved HB1.F3.CD neural stem cell carriers administered at the tumor resection bed in humans with recurrent malignant glioma.